Documented international enquiry on solid sedimentary fossil fuels; Coal: definitions, classifications, reserves-resources and energy potential - Alpern, B. (2006)
This paper deals with all solid sedimentary fossil fuels, i.e. coal, the main one for geological reserves and resources, peat, and oil shales. Definitions of coal ( < 50% ash) and coal seam (thickness and depth limits) are examined in view of an international agreement regarding new concepts for a common reserves and resources evaluation using the same nomenclature. The 50% ash limit, already adopted by UN-ECE for coal definition, allows the creation of a new category—the organic shales (50–75% ash)—comprising energetic materials still valuable for thermal use (coal shales) or to be retorted for oil production (oil shales). Geological relations between coals, oil shales, solid bitumen, liquid hydrocarbons, natural gas, and coalbed methane are also examined together with environmental problems. As a final synthesis of all topics, the paper discusses the problems related with a modern geological classification of all solid sedimentary fuels based on: various rank parameters (moisture content, calorific value, reflectance), maceral composition, and mineral matter content (and washability). Finally, it should be pointed out that the paper is presented as series of problems, some of them old ones, but never resolved until now. In order to facilitate the next generation of coal geologists to resolve these problems on the basis of international agreements, all sections begin with documented introductions for further questions opening an international enquiry. The authors hope that the answers will be abundant enough and pertinent to permit synthetic international solutions, valuable for the new millennium, with the help of interested consulted authorities, international pertinent organisations, and regional experts. D 2002 Elsevier Science B.V. All rights reserved.